Pengembangan Bahan Ajar Mata Kuliah Aqidah untuk Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah Universitas Muhammadiyah Riau - Wismanto, Wismanto; Yanti, Nova; Yapidus, Yapidus; Pranata, Hamdi; Deprizon, Deprizon (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2023)
The PGMI study program is a study program that produces prospective teacher graduates who have competency standards at the Madrasah Ibtidaiyah Teacher Education School. Based on the agreement with stakeholders who will later use PGMI graduates, then one of the competencies that must be mastered by a prospective MI teacher is the maturity of knowledge of Islamic Aqidah. This is due to the findings of several teachers at the MI School forbidding Islamic values that mix with superstition, bid'ah and superstition. This of course has a negative impact on the students' Aqidah, keeps them away from Allah's mercy, even without realizing that these actions can expel them from their Islam. The problem encountered in the learning process is that the number of special textbooks (primary books) that discuss Aqidah courses in accordance with the syllabus does not yet exist, there are only supporting books (secondary books) whose material is separate and independent from each sub-subject. teaching materials. To overcome this problem, it is necessary to develop a teaching material book (primary book) based on the needs and characteristics of students. To make the teaching material book, there will be a lot of material from existing secondary books and which have been used as learning resources for secondary students. This teaching material research was developed using the R2D2 Model (Reflective, Recursive, Design, and Development). In fact, it gave birth to a reference book for teaching materials with an ISBN.